Emotion classification based on text using Convolutional Neural Network / Mohammad Zulkarnain Moahmmed Ayub - Moahmmed Ayub, Mohammad Zulkarnain (2024)
This project not only contributes to the evolving landscape of natural language processing but also highlights the significance of leveraging advanced technologies, such as CNN, for emotion analysis. The findings of this research provide valuable insights into the potential of AI-driven models in understanding and categorizing emotions, paving the way for future advancements in sentiment analysis and emotion recognition. The endeavor emphasizes the critical role of responsible AI applications, especially in deciphering the intricate nuances of human emotions through textual data.